Estructuras vivientes el arte como experiencia plural : 23.11.2018-03.02.2019 = Living structures : art as plural experience - Fuenmayor, Jesús; Zapata, Cristóbal 1968- (Fundación Municipal Bienal de Cuenca, 2019)
The XIV Biennial was the largest of all those that have been held to date: because, in addition to the 48 proposals of the 52 artists that made up the official exhibition, the Biennial hosted two special exhibitions and five parallel exhibitions (three of which are part of this catalog). This large set of exhibitions was placed in 25 venues, that is, in almost all museums and galleries of the city, and in some neuralgic enclaves of the Historic Center.
Keywords: Bienal de Cuenca -- 14. -- 2018-2019 -- Cuenca, Ecuador; Geschichte 2018-2019; Geschichte 1964-2019; Kunst; Kunstausstellung; Erfahrung; Installation -- Kunst; Cuenca; Ausstellungskatalog -- 23.11.2018-03.02.2019 -- Cuenca, Ecuador; Bildband